QGIS Plugins for Web Maps Creation Monitoring with GIS Cloud (Case Study) - Albina Basholl, Erjola Cenaj, Elda Maraj , Shkelqim Kuka (South Eastern European Journal of Public Health, 2025)
Since most GIS users are not web programmers, it might be difficult to produce a web map that is as good as one made in a GIS environment. Thankfully, there exist tools that make it simple to convert your QGIS work to online maps. QGIS is an open-source, free geographic information system (GIS) programme. QGIS is compatible with Linux, macOS, and Windows. QGIS plugins give the QGIS programme access to free extra features. This paper takes a look of the publishing capabilities of two QGIS plugins (QGIS Cloud, GIS Cloud Publisher) to create Web Maps. The ability to automate processes without a programming language is made possible by the availability of plugins in open source GIS applications. The chosen plugins for testing and comparison make it possible to create Web Maps and can be very helpful for users who are not familiar with programming languages to develop a basic Web Map from scratch. Following this conversation, we have selected the Gis Cloud platform for implementation in a project focused on mosquito monitoring and control. This research discusses the application of GIS Cloud in monitoring mosquito populations, its benefits, methodology, and a case study that illustrates its effectiveness in mosquito control. The public health department collected data from field surveys and integrated it within GIS Cloud. GIS Cloud gives our users access to the entire potential of desktop GIS, enabling tasks like geographical analysis, spatial intelligence, the production of personalised mapping reports, and the publication of geographic analysis online. Through the analysis of spatial data, health officials could establish community initiatives to mitigate breeding places, resulting in a substantial reduction of mosquito populations in designated locations.